Pengembangan Aplikasi Pendataan Ketersediaan Barang Studi Kasus YM Autowheel Berbasis Android - Muhammad Matrix Indra Nawawi Daeng Parani; Yulius Denny Prabowo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to help Ym Autowheel in overcoming the existing problems in terms of recording the availability of goods. Publications regarding the status of availability of goods can be accessed in real time based on android. This application uses the Rational Unified Process (RUP) research methodology. This application has 2 users, namely admin and user, the admin must register first to add a brand or stock so that the stock can be displayed to the user. This application provides an alternative in managing stock items, storage is done using an internet connection and using hosting as a storage medium. The result of this research is the Android-based Ym Autowheel application.